Effect of anti-tuberculosis treatment on thyroid profile in newly detected smear positive pulmonary tuberculosis cases - Varghese, Vimi; Menon, K. Surendra; Green, Siva Ranganathan (International Journal of Advances in Medicine, 2018)
Background: Tuberculosis being a systemic disease and has a capacity for wide spread dissemination. Present study aims to identify the effects of antituberculous treatment on thyroid profile in new smear positive pulmonary tuberculosis cases. Methods: This study was conducted among 60 new smear positive pulmonary tuberculosis cases attending pulmonary medicine OPD from May 2015 to April 2017. Thyroid function test in the form of free T3, free T4 and TSH was measured before initiating Anti tuberculosis treatment (ATT), at 3 months and at the end of 6 months. Results: Out of 60 patients enrolled in present study, majority were males. Diabetes mellitus was the major co morbidity. Sick euthyroid was found to have decreasing trend during the course of treatment, and hypothyroidism was found to be increasing trend end of 6 months. Conclusions: The common Thyroid Dysfunction seen during the study period was Hypothyroidism and Sick euthyroid. Anti-tuberculous medication preferably Rifampicin probably would explain the cause for these thyroid dysfunctions noticed during the study time. And those patients with significant hypothyroid need to started on thyroid supplements. Among the drugs used for treatment, rifampicin was probably the cause for thyroid dysfunction noticed during the course of treatment. Hence, authors recommend that these patients should be started on thyroid supplements after the diagnosis of significant hypothyroidism.